Construindo o início da docência: uma doutora em educação vai-se tornando professora dos anos iniciais do ensino fundamental. - Rocha, Gisele Antunes (Universidade Federal de São Carlos, 2005)
This investigation, of qualitative nature, sought to know how a Doctor in Education becomes a teacher of the starting grades of elementary school and was organized around the following questions: How does the learning of a Doctor in Education who is beginning to teach the starting grades of elementary school characterize itself? Are there differences (or not) between the professional learning of this teacher and the other beginner teachers, without the same academic experience, investigated on other studies? The research was developed in two phases. On a first moment, I followed the building of a beginner teacher s practice by means of her narratives written during the first semester of the school year and, near the end of the year, I brought back questions shown in her registries on two interview sessions. On a second moment, when the teacher was already working in another teaching institution, I got to talk to her again on three interview sessions, to share my interpretation of the data, clarify some aspects and give voice to her ideas and analysis. This way, I met at the same time the methodological (this kind of study demands a comprehension of the meaning attributed to the data by the teacher) and ethical dimensions (the teacher had reached a more advanced level on her studies than mine, and on these studies she was the subject). The data were organized on the following analysis focuses: difficulty in managing time and the available conditions versus the specific learning difficulties of the students, difficulty to take control of the situation and learning sources of professional teaching. For the data analysis, I took as theoretical reference studies about the building of teaching beginning, teaching knowledge, the relationship between thought and action, and five other correlated researches. The results indicated that even the teacher being a Doctor in Education, her first teaching year was a period marked by great difficulties and doubts, such as indicated by the literature in the area. They revealed that teaching knowledge is temporal, plural, existential, social and pragmatic, as said Tardif and Raymond; confirmed the idea that the relationship between thought and action is not linear, given that the origin and the direction of the action must be searched in particular situational conditions in which practice is made, confirming the ideas of Zabalza; highlighted the importance of relationship with the students, pairs, theoretical studies and institutional politics as sources of learning for professional teaching. It was possible to detect points that revealed, by the data, some differentials brought by the fact of the teacher being a Doctor in Education. Apparently, this fact was more highlighted on the conceptions than on the ways of acting. The importance of support to the teachers on beginning careers by the school was very highlighted as it is also said by the literature in order to take the teachers formation process as a collective and continuous construction and, mainly, in order to keep the students of these teachers from suffering the consequences of their nonexpertise.
Building the teaching beginning: a Doctor in Education becomes a teacher of the starting grades of elementary school.
Keywords: Professores - formação; Aprendizagem profissional da docência; Professores iniciantes; CIENCIAS HUMANAS::EDUCACAO